Karakteristik Kimia Dan Sensori Produk Ikan Terasak (Escualosa Thoracata) Asin Pada Industri Rumah Tangga Di Kecamatan Lekok Kabupaten Pasuruan - Utari, Siska Putri; Ikerismawati, Senja (Lempuk: Jurnal Ilmu Kelautan dan Perikanan, 2022)
Tasted fish are small fish that live in the ocean. Tasted fish is managed as a food that is often favored by the community, namely salted tasted fish. Salted fish is a type of food that is very popular with the community. In addition to having a good taste, this food also has a high protein and calcium content so that it can meet the nutritional needs of the community. This study aims to determine the chemical characteristics of salted tasted fish products (Escualosa thoracata) in Lekok District, Pasuruan Regency, and to determine the results of sensory characteristics of salted tasted fish products (Escualosa thoracata) in Lekok District, Pasuruan Regency. The method of data collection in this study was by observing the observed parameters, namely water content, ash content, salt content, and sensory. This research was conducted at the Food Engineering Laboratory, Yudharta University Pasuruan, Food Chemistry & Microbiology Laboratory, Yudharta Pasuruan University and Nutrition Laboratory, Health Nutrition Department, Faculty of Public Health, Airlangga University, Surabaya. This research was conducted from April to June 2022. The results of this study are that the chemical characteristics have met the standard of SNI 8273: 2016 except for chemical characteristics (salt content) several home industries have not met the standard of SNI 8273: 2016 Sensory characteristics have met the standard of SNI 8273: 2016 except for sensory characteristics (Textures) that do not meet the standard of SNI 8273: 2016